Species of the Maera-clade collected from Japan. Part 4: addenda to genera Maera Leach, 1814 and Quadrimaera Krapp-Schickel & Ruffo, 2000, with revised keys to Japanese species of the clade (Crustacea: Amphipoda: Maeridae) - Ariyama, Hiroyuki; Kodama, Masafumi; Tomikawa, Ko (Zootaxa, 2020)
Two new species of Maera Leach, 1814 and Quadrimaera Krapp-Schickel & Ruffo, 2000 included in the Maera-clade are described from Japan. Maera denticoxa sp. nov. was collected from Iwate and Hokkaido Prefectures and can be distinguished from its congeners by the small notches on the posteroventral margins of coxae 1–6. Quadrimaera angulata sp. nov. from north of Tanegashima Island in Kagoshima Prefecture is characterized by the distal tooth on the mandibular palp article 1, the rounded palm of the female gnathopod 2, and the angular posterodistal margin of the pereopod 7 basis. Keys to Japanese species of the Maera-clade are provided. In total, seventeen species included in the clade occur in Japan.